Light regulation of type IV pilus-dependent motility by chemosensor-like elements in Synechocystis PCC6803 - Bhaya, Devaki (The National Academy of Sciences, 2001)
To optimize photosynthesis, cyanobacteria move toward or away from a light source by a process known as phototaxis. Phototactic movement of the cyanobacterium Synechocystis PCC6803 is a surface-dependent phenomenon that requires type IV pili, cellular appendages implicated in twitching and social motility in a range of bacteria. To elucidate regulation of cyanobacterial motility, we generated transposon-tagged mutants with aberrant phototaxis; mutants were either nonmotile or exhibited an “inverted motility response” (negative phototaxis) relative to wild-type cells. Several mutants contained transposons in genes similar to those involved in bacterial chemotaxis. Synechocystis PCC6803 has three loci with chemotaxis-like genes, of which two, Tax1 and Tax3, are involved in phototaxis. Transposons interrupting the Tax1 locus yielded mutants that exhibited an inverted motility response, suggesting that this locus is involved in controlling positive phototaxis. However, a strain null for taxAY1 was nonmotile and hyperpiliated. Interestingly, whereas the C-terminal region of the TaxD1 polypeptide is similar to the signaling domain of enteric methyl-accepting chemoreceptor proteins, the N terminus has two domains resembling chromophore-binding domains of phytochrome, a photoreceptor in plants. Hence, TaxD1 may play a role in perceiving the light stimulus. Mutants in the Tax3 locus are nonmotile and do not make type IV pili. These findings establish links between chemotaxis-like regulatory elements and type IV pilus-mediated phototaxis.